The Limits To Creativity In Education: Dilemmas For The Educator - Craft, Anna (British journal of educational studies, 2003)
Since the end of the 1990s, creativity has become a growing area of interest once more within education and wider society. In England creativity is now named within the school curriculum and in the curriculum for children aged 3-5. There are numerous government and other initiatives to foster individual and collective creativity, some of this through partnership activity bringing together the arts, technology, science and the social sciences. As far as education is concerned, this growth in emphasis and value placed on encouraging creativity can be seen as being in stark contrast with the government policy prevalent from the late 1980s onward. One of the underpinning themes and justifications for this re-kindling of interest in fostering creativity is that the individual and collective empowerment which is fostered by the development of creative skill is seen to be a good thing at the social and economic level in particular (Craft, 2002). These justifications have been discussed elsewhere (Jeffrey and Craft, 2001). But an important question to ask is, how desirable are the cultural norms of continual change and innovation in Western society? This paper examines some possible social, environmental, cultural and ethical limits to creativity, in the context of educating for creativity (NACCCE, 1999). It argues that the notion of creativity may be value- and culture-specific and that this poses the so-called liberal educator with various dilemmas of principle and pedagogy, which are explored.